Assessment of cognitive safety in clinical drug development. Issue 3 (March 2016) - Roiser, Jonathan P.; Nathan, Pradeep J.; Mander, Adrian P.; Adusei, Gabriel; Zavitz, Kenton H.; Blackwell, Andrew D.
Highlights: Commonly-used medications are associated with cognitive impairment. Cognitive safety is rarely investigated in randomised controlled trials (RCTs). Statistical power is a critical issue when assessing cognitive impairment in RCTs. Cognitive assessments in RCTs need to use appropriate and sensitive measurements. Benchmarking is a useful method for quantifying and communicating cognitive risk. Abstract : Cognitive impairment is increasingly recognised as an important potential adverse effect of medication. However, many drug development programmes do not incorporate sensitive cognitive measurements. Here, we review the rationale for cognitive safety assessment, and explain several basic methodological principles for measuring cognition during clinical drug development, including study design and statistical analysis, from Phase I through to postmarketing. The crucial issue of how cognition should be assessed is emphasized, especially the sensitivity of measurement. We also consider how best to interpret the magnitude of any identified effects, including comparison with benchmarks. We conclude by discussing strategies for the effective communication of cognitive risks. Abstract : This keynote review outlines the rationale, study design, and methods for cognitive safety assessment during clinical drug development, as well as strategies for interpreting and communicating cognitive risk.